Working memory in pediatric frontal lobe epilepsy. Issue 2 (3rd April 2021) - van den Berg, Lydia; de Weerd, Al; Reuvekamp, Marieke; Hagebeuk, Eveline; van der Meere, Jaap
Abstract: Thirty-two children with frontal lobe epilepsy (FLE) were assessed using different working memory measures. In addition, parents and teachers completed the working memory scale of the Behavioral Rating Inventory of Executive Functioning (BRIEF) to assess the children's "daily life behavior." Results suggested minimal working memory deficits as assessed with performance-based measures. However, the BRIEF showed more working memory deficits suggesting that, on a daily life level, working memory problems seem to be associated with FLE. We discuss why the results of the performance-based measures are not consistent with results of the BRIEF. Highlights: Parents as well as teachers report working memory dysfunction in daily life to the same extent. Performance based measures show minimal deficits of working memory. Correlation between working memory tasks and proxy measures are low.